2020
DOI: 10.37689/acta-ape/2020ao0141
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida, adesão e indicadores clínicos em pessoas vivendo com HIV

Abstract: Qualidade de vida, adesão e indicadores clínicos em pessoas vivendo com HIV Quality of life, adherence and clinical indicators among people living with HIV Calidad de vida, adherencia e indicadores clínicos en personas que viven con el VIH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
18

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 22 publications
0
8
0
18
Order By: Relevance
“…A study from Desta (2020) revealed that more than half of participants adhering to ARVs were related to having better global scoresfrom life quality (Desta et (Lahai et al, 2020), (Primeira et al, 2020), (Xiao et al, 2019), (Nyongesa et al, 2018), (Reis et al, 2020), (Sabino et al, 2020). Quality of life globally (Reis et al, 2020), (Xiao et al, 2019), (Desta et al, 2020), (Bulali et al, 2018) Sexual function / sex (Sabino et al, 2020), (Primeira et al, 2020) Virus suppression (Kagee et al, 2016), (Tran et al, 2018) Viral load was decreased, CD 4, lymphocytewere increased, disease progression was decreased, the opportunistic infection was decreased, body immune was increased. (Kagee et al, 2016), (Primeira et al, 2020), (Xiao et al, 2019), (Reis et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A study from Desta (2020) revealed that more than half of participants adhering to ARVs were related to having better global scoresfrom life quality (Desta et (Lahai et al, 2020), (Primeira et al, 2020), (Xiao et al, 2019), (Nyongesa et al, 2018), (Reis et al, 2020), (Sabino et al, 2020). Quality of life globally (Reis et al, 2020), (Xiao et al, 2019), (Desta et al, 2020), (Bulali et al, 2018) Sexual function / sex (Sabino et al, 2020), (Primeira et al, 2020) Virus suppression (Kagee et al, 2016), (Tran et al, 2018) Viral load was decreased, CD 4, lymphocytewere increased, disease progression was decreased, the opportunistic infection was decreased, body immune was increased. (Kagee et al, 2016), (Primeira et al, 2020), (Xiao et al, 2019), (Reis et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 15 articles selected in the line review published between 2016 and 2020 are international journals originating from the country (Brazil = 2); (Betancur et al, 2017), (Sabino et al, 2021), (Africa = 3); (Nyongesa et al, 2018), (Bulali et al, 2018), (Kagee et al, 2016), (China = 2); (Xiao et al, 2019), (Tran et al, 2018), (Indonesian = 2) (Suryana et al, 2019), (Khotimah et al, 2018), (Eutopia = 2) (Asrat et al, 2020), (Desta et al, 2020), (Indian = 1) (Sarkar et al, 2019), (USA = 3), (Lahai et al, 2020), (Reis et al, 2019), (Primeira et al, 2020). The total number of respondents in this review were 5,416 respondents, with a total population involved between 83 and 1395 participants.…”
Section: Partisipant Characteristicmentioning
confidence: 99%
See 3 more Smart Citations